체중조절 건강기능식품에 대한 소비자 인식조사 - 박미영(Mi-Young Park); 공경혜(Kyung-Hye Kong); 이명숙(Myoungsook Lee) (동아시아식생활학회지, 2019)
As Korean society has recently entered the stage of aging, there has been considerable interest in health food products to prevent adult diseases and improve health with diet. This study is to examine the consumer awareness of health functional foods. From November 2013 to April 2014, adults living in northern Seoul were surveyed on general matters, physical condition and opinions, weight control and recognition of general health functional foods. The subjects were 212 adults (75 men and 137 women) who completed the validated questionnaire The study was conducted with IRB approval from Sungshin Women's University. Eighty-two percent of the respondents wanted to lose weight, 75% had weight loss experience and preferred exercise therapy for a weight control method and 47% of diet participants relied on health functional foods. In addition, both men and women answered that they had failed to control their weight because of a lack of will, and that the most effective way was exercise. Overall, 79% and 61% of people who had experience in searching information of health functional foods through internet websites considered healthy food as food. Sixty-seven percent of the respondents had experience in purchasing health functional foods, purchased them to relieve their fatigue, supplement nutrition, control their weight, prevent and treat diseases, boost their stamina, beauty, and prevent aging. In conclusion, consumers who prefer weight-control health products said, “As the efficacy and main ingredients (38%) are considered important when purchasing, it is necessary to provide accurate information (38%) and improve the quality of products (28%).” Therefore, the government or manufacturers should strive to promote consumer’s informed choice improve the quality of the product. KCI Citation Count: 9